2020
DOI: 10.1111/acps.13222
|View full text |Cite
|
Sign up to set email alerts
|

Decreased oxytocin plasma levels and oxytocin receptor expression in borderline personality disorder

Abstract: ıaz-Mars a M, Leza JC. Decreased oxytocin plasma levels and oxytocin receptor expression in borderline personality disorder. Introduction: Borderline personality disorder (BPD) is characterized by intense affective reactions with underlying social and interpersonal cognitive deficits. Oxytocin has largely been associated with both stress regulation and social cognition in psychiatric patients and in nonclinical populations in previous studies. Finally, abnormal oxytocin levels have been preliminary reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Through its connections with the dopaminergic reward system, oxytocin is hypothesized to regulate attention to social cues by guiding the individual as to whom to align with, through signalling which social cues and interactions are rewarding and should be selectively attended to (Shamay-Tsoory and Abu-Akel, 2016). Impairments in the attachment system in BPD, as evidenced by high reports of attachment insecurity (Agrawal et al, 2004) and dysfunction of the oxytocin system (Carrasco et al, 2020), may leave BPD patients without a "filter" to allow them to decide which interactions are safe and rewarding to tune into. Indeed, the administration of intranasal oxytocin was found to normalize approach motivation (Domes et al, 2019) and approach-avoidance behaviour (Schneider et al, 2020) in response to socio-emotional cues in individuals with BPD.…”
Section: A New Model Of Impairments In Switching Between Self and Other Representations And Interpersonal Attunement In Bpdmentioning
confidence: 99%
“…Through its connections with the dopaminergic reward system, oxytocin is hypothesized to regulate attention to social cues by guiding the individual as to whom to align with, through signalling which social cues and interactions are rewarding and should be selectively attended to (Shamay-Tsoory and Abu-Akel, 2016). Impairments in the attachment system in BPD, as evidenced by high reports of attachment insecurity (Agrawal et al, 2004) and dysfunction of the oxytocin system (Carrasco et al, 2020), may leave BPD patients without a "filter" to allow them to decide which interactions are safe and rewarding to tune into. Indeed, the administration of intranasal oxytocin was found to normalize approach motivation (Domes et al, 2019) and approach-avoidance behaviour (Schneider et al, 2020) in response to socio-emotional cues in individuals with BPD.…”
Section: A New Model Of Impairments In Switching Between Self and Other Representations And Interpersonal Attunement In Bpdmentioning
confidence: 99%
“…Similarly, in another study, it was shown that there was a decrease in the plasma oxytocin levels in women diagnosed with BPD, and it was concluded that the dysregulation in the oxytocin system may be an important underlying factor for BPD. 9 Along these lines, in another study, it was shown that there was a decrease in the oxytocin levels as well as in oxytocin receptor protein expression in patients with BPD compared to the control group [ 17 , 18 ]. It has been reported that the low oxytocin levels may be a factor in the abnormal response given to stress and the bottom-up and top-down dysregulation of emotional systems, which is characteristic of BPD [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only are oxytocin levels lower in BPD, but the oxytocin receptor (OXTR) expression is decreased as well, showing the role of oxytocin and its receptor in this disorder [9]. It is important to not see OXTR from an angle of "diathesis-stress"; we should rather see it from an angle of "differential susceptibility" (also known as "plasticity").…”
Section: Oxytocin Receptor and Its Genesmentioning
confidence: 99%